Analysis of Heat Treatment Results of Ti6Al7Nb for Application as Total Hip Arthroplasty Component Material - Suhendra, Nandang; Setiawan, Harun; Purwati, Henny; Lukmana, Lukmana (Green Publisher Indonesia, 2022)
This research is a literature study on Ti-6Al-7Nb material after having heat treatment. This study aims to analyze the results of selected articles reporting the effect of Ti-6Al-7Nb heat treatment. The research method used in this literature study is a qualitative descriptive method. Only several article results from analyses were reviewed that meet the requirement for implementation for future research topics related to materials for total hip arthroplasty. Data sources are obtained through library research techniques (literature study), which refers mainly to online sources, such as scientific journals, websites, and news from trusted sources. The results concluded that materials preparation techniques, heat treatment methods, and results analysis reported in those articles should be appropriate in this paper review. It was suggested from the literature that we need to anticipate that the martensitic phase does not cause significant changes in the Titanium alloys' properties. Moreover, the heat treatment method for α-type Titanium alloys is ineffective; namely, the heat treatment of Titanium alloys is mainly used for α+β-type Titanium alloys. The heat treatment should avoid the formation of the ω phase because constructing the ω phase will make Titanium alloys brittle.